Metformin and soybean-derived bioactive molecules attenuate the expansion of stem cell-like epithelial subpopulation and confer apoptotic sensitivity in human colon cancer cells - Montales, Maria Theresa E.; Simmen, Rosalia C. M.; Ferreira, Ederlan S.; Neves, Valdir A. [UNESP]; Simmen, Frank A. (Genes & Nutrition, 2015)
Colorectal cancer (CRC) is a disease whose genesis may include metabolic dysregulation. Cancer stem cells are attractive targets for therapeutic interventions since their aberrant expansion may underlie tumor initiation, progression, and recurrence. To investigate the actions of metabolic regulators on cancer stem cell-like cells (CSC) in CRC, we determined the effects of soybean-derived bioactive molecules and the anti-diabetes drug metformin (MET), alone and together, on the growth, survival, and frequency of CSC in human HCT116 cells. Effects of MET (60 μM) and soybean components genistein (Gen, 2 μM), lunasin (Lun, 2 μM), β-conglycinin (β-con, 3 μM), and glycinin (Gly, 3 μM) on HCT116 cell proliferation, apoptosis, and mRNA/protein expression and on the frequency of the CSC CD133(+)CD44(+) subpopulation by colonosphere assay and fluorescence-activated cell sorting/flow cytometry were evaluated. MET, Gen, and Lun, individually and together, inhibited HCT116 viability and colonosphere formation and, conversely, enhanced HCT116 apoptosis. Reductions in frequency of the CSC CD133(+)CD44(+) subpopulation with MET, Gen, and Lun were found to be associated with increased PTEN and reduced FASN expression. In cells under a hyperinsulinemic state mimicking metabolic dysregulation and without and with added PTEN-specific inhibitor SF1670, colonosphere formation and frequency of the CD133(+)CD44(+) subpopulation were decreased by MET, Lun and Gen, alone and when combined. Moreover, MET + Lun + Gen co-treatment increased the pro-apoptotic and CD133(+)CD44(+)-inhibitory efficacy of 5-fluorouracil under hyperinsulinemic conditions. Results identify molecular networks shared by MET and bioavailable soy food components, which potentially may be harnessed to increase drug efficacy in diabetic and non-diabetic patients with CRC.
Keywords: Colon cancer; Genistein; Lunasin; Metformin; Soy; Stem-like cell